2021
DOI: 10.1088/1674-1056/ac0037
|View full text |Cite
|
Sign up to set email alerts
|

Realization of semiconducting Cu2Se by direct selenization of Cu(111)*

Abstract: Bulk group IB transition-metal chalcogenides have been widely explored due to their applications in thermoelectrics. However, a layered two-dimensional form of these materials has been rarely reported. Here, we realize semiconducting Cu2Se by direct selenization of Cu(111). Scanning tunneling microcopy measurements combined with first-principles calculations allow us to determine the structural and electronic properties of the obtained structure. X-ray photoelectron spectroscopy data reveal chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In experimental synthesis [39], monolayer Cu 2 Se have been successfully produced, and intriguingly, they exhibit the characteristics of a 2D NLSM. As illustrated in figure 1(a), these nanosheets adopt a hexagonal lattice structure, with each unit cell containing two copper (Cu) atoms and one selenium (Se) atom.…”
Section: Topological Properties Of Cu 2 Sementioning
confidence: 99%
“…In experimental synthesis [39], monolayer Cu 2 Se have been successfully produced, and intriguingly, they exhibit the characteristics of a 2D NLSM. As illustrated in figure 1(a), these nanosheets adopt a hexagonal lattice structure, with each unit cell containing two copper (Cu) atoms and one selenium (Se) atom.…”
Section: Topological Properties Of Cu 2 Sementioning
confidence: 99%
“…The authors also reported a similar scheme for realizing environmentally stable TiSe 2 and other ambient-sensitive selenides. Starting with another transition metal, Yang et al reported the synthesis of semiconducting Cu 2 Se via selenization of Cu(111) in ultrahigh vacuum, resulting in a layered phase of Cu 2 Se that was markedly distinct from its regular unlayered bulk phase . This 2D Cu 2 Se structure exhibited a band gap of 0.74 eV, again underscoring that phases distinct from naturally occurring materials can emerge using morphotaxial approaches.…”
Section: Morphotaxial Anionic Modificationsmentioning
confidence: 99%
“…The confusion of ABS and Anthracnose, or Alternaria species and Colletotrichum species, for the symptoms of citrus brown spot has lasted for over a decade in China, but still lacks a conclusion [8,9]. ABS was first observed in 2003, and reported in 2010, in Yunnan Province, China [10].…”
Section: Introductionmentioning
confidence: 99%
“…ABS was first observed in 2003, and reported in 2010, in Yunnan Province, China [10]. After that, the disease has been successively reported as an outbreak in several other citrus production areas in China, such as Chongqing [7], Zhejiang [11], Guangxi [9], and Fujian [12]. However, the diseased citrus trees (C. reticulata var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation